2020
DOI: 10.1371/journal.pone.0239945
|View full text |Cite
|
Sign up to set email alerts
|

A climate adaptation strategy for Mai Po Inner Deep Bay Ramsar site: Steppingstone to climate proofing the East Asian-Australasian Flyway

Abstract: The ecological functionality of the East Asian-Australasian Flyway is threatened by the loss of wetlands which provide staging and wintering sites for migrating waterbirds. The disappearance of wetland ecosystems due to coastal development prevents birds from completing their migrations, resulting in population declines, and even an eventual collapse of the migration phenomenon. Coastal wetlands are also under threat from global climate change and its consequences, notably sea level rise (SLR), extreme storm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Habitat transformation along the coast of China, especially in the Yellow Sea area, has caused prominent declines of several species; this is supported by the studies revealing declines of species that rely on Yellow Sea as essential stopover sites at wintering sites in Japan, Australia, and New Zealand (Amano et al, 2010;Murray et al, 2015Murray et al, , 2017Studds et al, 2017). Besides habitat transformation, waterbirds of the EAAF also experience a wide range of other threats (Wang et al, 2018), including hunting (Gallo-Cajiao et al, 2020), alien invasive species (Gan et al, 2009), pollution (Zhao et al, 2016), and climate change (Iwamura et al, 2013;Wikramanayake et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Habitat transformation along the coast of China, especially in the Yellow Sea area, has caused prominent declines of several species; this is supported by the studies revealing declines of species that rely on Yellow Sea as essential stopover sites at wintering sites in Japan, Australia, and New Zealand (Amano et al, 2010;Murray et al, 2015Murray et al, , 2017Studds et al, 2017). Besides habitat transformation, waterbirds of the EAAF also experience a wide range of other threats (Wang et al, 2018), including hunting (Gallo-Cajiao et al, 2020), alien invasive species (Gan et al, 2009), pollution (Zhao et al, 2016), and climate change (Iwamura et al, 2013;Wikramanayake et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Cabo Roja Salt Flats National Wildlife Refuge on the island of Puerto Rico is only 522 ha but is a critical stopover site for migrating shorebirds in the Caribbean [37] and is part of the Western Hemisphere Shorebird Reserve Network. The Mai Po Marshes nature reserve at 113 ha is a small wetland located in Hong Kong and is an internationally significant wetland that is actually a shallow estuary supporting globally important numbers of wetland birds, which chiefly arrive in winter and during spring and autumn migrations, including over 55,000 migrating birds such as Saunders's gull (Chroicocephalus saundersi), a quarter of the world's Black-faced spoonbill (Platalea minor) population, and significant numbers of Spoon-billed sandpiper (Calidris pygmaea) [38].…”
Section: A Typology Of Communicating and Planning For The Roles Of Sm...mentioning
confidence: 99%
“…Nevertheless, SLAMM has been shown to be effective in simulating wetland changes in other studies of tropical coastal regions (Li et al 2015;Payo et al 2016;Wikramanayake et al 2020;Dang et al 2022). Wu et al (2015) suggested that SLAMM could be an effective approach to simulate coastal wetland changes with the use of accurate data and meaningful evaluation of the simulation outcome.…”
Section: Model Accuracies and Uncertaintiesmentioning
confidence: 99%
“…SLAMM uses high-resolution spatial data to simulate wetland changes in response to SLR at landscape scales and so is capable of predicting wetland dynamics in response to SLR with higher accuracy in comparison to other methods (Craft et al 2009;Clough et al 2010;Wu et al 2015). The model has been successfully applied in the USA (Mcleod et al 2010) and some other regions around the world (Akumu et al 2011;Li et al 2015;Wu et al 2015;Payo et al 2016;Fernandez-Nunez et al 2019;Prado et al 2019;Raw et al 2020;Wikramanayake et al 2020;Dang et al 2022). Amongst these previous studies, Dang et al (2022) demonstrated that SLAMM is capable of simulating changes of mangrove wetlands in response to SLR in the Mekong Delta by using elevation data with high-vertical accuracy and precise localized parameters.…”
Section: Introductionmentioning
confidence: 99%